{(1R,3S)-2-Benzyl-6,7-dimethoxy-1-phenyl-1,2,3,4-tetrahydroisoquinolin-3-yl}diphenylmethanol - Glenn E.M. Maguire; Hendrik G. Kruger; Thavendran Govender; Tricia Naicker (Acta Crystallographica Section E, 2010)
In the title compound, C37H35NO3, a precursor to novel chiral catalysts, the N-containing six-membered ring assumes a half-chair conformation. Intermolecular C—H...O hydrogen bonds link the molecules in the crystal structure.